MEMBERI SALAM KEPADA NON MUSLIM (PERSPEKTIF MODERASI BERAGAMA) - Husaini, Alpahmi (UIN Sumatera Utara Medan, 2024)
This study examines greeting non-Muslims from the perspective of religious moderation, providing new insights into how religion, in this case Islam, can play a role in creating interfaith dialogue. This is important for building a more tolerant, respectful society, and more able to live side by side peacefully within the framework of diversity. This study uses a qualitative approach method to try to understand deeper phenomena, such as the views of society and religious leaders regarding greeting non-Muslims within the framework of religious moderation. The findings in this study of greeting non-Muslims and responding to their greetings have different opinions among scholars. Ibn Abbas Abu Umamah Ibn Wahab Ibn Abi Syaibah allows initiating greetings to non-Muslims, while the al-Shafi'i school of thought, Imam Malik Imam Nawawi do not allow it, but from the perspective of religious moderation, greeting non-Muslims has a positive impact on social relations between religious communities. This practice not only reflects Islamic teachings on peace and tolerance, but also strengthens more inclusive social ties in a pluralistic society.